2022 EDEN ISS Antarctic Greenhouse Project Report - Bunchek, Jess; Hummerick, M. (2022)
EDEN ISS is a greenhouse container near the German Neumayer Station III in Antarctica. The greenhouse was designed and is operated by the German Aerospace Center (DLR) Institute of Space Systems out of Bremen, Germany. Originally funded by a European Union Horizons 2020 grant, EDEN ISS was installed at Neumayer in early 2018 and was operated for four overwintering seasons until the beginning of 2022. For the 2021 season, NASA Kennedy scientist Jess Bunchek operated EDEN ISS as an overwinterer at Neumayer. While atypical for a scientific project report, the following is written in first-person perspective to better communicate the observations that accompany the operations and collected data.